2021
DOI: 10.3389/fmats.2021.642099
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and Limitations of Surface Analysis Techniques on Plasma-Treated Arabidopsis thaliana Seeds

Abstract: Surface characterization of plasma-treated seeds has made significant progress over the last decade. Most papers in the literature use scanning electron microscopy (SEM) and contact angle goniometry to investigate surface modifications. However, very few papers address the chemical modifications to the seed coat after plasma treatment. Here, a summary of the methods used to analyze plasma-treated seeds is presented, such as SEM, contact angle goniometry, energy-dispersive X-ray spectroscopy (EDX), X-ray photoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Since we observed that particular plasma conditions yielded a statistically significant effect on germination, plasma chemistry was compared between these conditions to identify the reason for this effect. Although a previous study used five surface analysis techniques on plasma-treated seeds, including SEM images [ 3 ], the focus of this study was to analyze plasma chemistry. Typical absorption spectra in the mid-infrared range of 2500–500 cm −1 , with 4 cm −1 resolution and 20 s acquisition periods are shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Since we observed that particular plasma conditions yielded a statistically significant effect on germination, plasma chemistry was compared between these conditions to identify the reason for this effect. Although a previous study used five surface analysis techniques on plasma-treated seeds, including SEM images [ 3 ], the focus of this study was to analyze plasma chemistry. Typical absorption spectra in the mid-infrared range of 2500–500 cm −1 , with 4 cm −1 resolution and 20 s acquisition periods are shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Through seed surface modifications, it is also possible to alter ion homeostasis, which was indicated by downregulation in ion transport activity in Figure 8 A. Previous studies have shown ion redistribution after plasma treatment in cations such as calcium, magnesium, or potassium, migrating into the interior of the seed or being enriched on the surface [ 43 , 44 ]. This, however, could also be interpreted by the seed as damage and, therefore, could be a symptom of a plant stress response.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of plasma–seed treatments as a potential seed processing technology are reviewed by Waskow et al, [ 14 ] and some of the corresponding plasma devices found in the literature are listed in Figure 3. Among the papers cited in the present study, the most common plasma sources include planar dielectric barrier discharges (DBDs) in various forms as shown in Figure 3(1), [ 11–64 ] followed by DBD plasma jets as shown in Figure 3(2) [ 10,36,65–74 ] ; low‐pressure plasma in a vacuum chamber as shown in Figure 3(3) [ 28,43,75–89 ] ; and less common devices such as gliding arcs, [ 9,43,76,90 ] and corona arrays as shown in Figure 3(4). [ 43,91,92 ]…”
Section: Plasma Devicementioning
confidence: 99%
“…The various types of plasma sources in Figure 3 can be summarized as follows: A DBD generates plasma by time‐varying high voltage (kV) between two electrodes; the dielectric barrier is to prevent arcing between electrodes that could otherwise occur following the electrical breakdown of the gas. The planar DBD may generate the plasma in the volume of gas between opposing electrodes (VDBD), [ 12,17–41 ] or on the surface of a dielectric adjacent to the electrode edges (SDBD), [ 11,42–53 ] or with embedded electrodes (diffuse coplanar surface barrier discharge [DCSBD]). [ 54–59 ] In a plasma jet, there is usually a gas flowing in a thin tube with a DBD excitation that can be pulsed DC, or continuous AC, or radiofrequency (RF).…”
Section: Plasma Devicementioning
confidence: 99%
See 1 more Smart Citation